The Earliest Form and Function of the ‘Admonitio synodalis’ - West, Charles (Frühmittelalterliche Studien, 2023)
This article examines a text known as the ‘Admonitio synodalis’ as evidence for episcopal expectations of local priests in the tenth and eleventh centuries. The ‘Admonitio’ is generally considered a stable text that represented and fostered continuity within the Church, but this article highlights instead its early development. It begins by identifying a previously unedited version of the text found in some tenth-century manuscripts, arguing that this long recension is the closest to the original form. It then turns to how the text was adapted in the tenth century, notably by Bishop Rather of Verona. It finally examines the changes made to the text when it was incorporated into the liturgy of synodal ordines in the early eleventh century. A transcription of the tenth-century recension, based on a Brussels manuscript, is provided as an appendix.